A continental‐scale assessment of variability in leaf traits: Within species, across sites and between seasons. (6th April 2018) - Bloomfield, Keith J.; Cernusak, Lucas A.; Eamus, Derek; Ellsworth, David S.; Colin Prentice, I.; Wright, Ian J.; Boer, Matthias M.; Bradford, Matt G.; Cale, Peter; Cleverly, James; Egerton, John J. G.; Evans, Bradley J.; et al.
Abstract: Plant species show considerable leaf trait variability that should be accounted for in dynamic global vegetation models (DGVMs). In particular, differences in the acclimation of leaf traits during periods more and less favourable to growth have rarely been examined. We conducted a field study of leaf trait variation at seven sites spanning a range of climates and latitudes across the Australian continent; 80 native plant species were included. We measured key traits associated with leaf structure, chemistry and metabolism during the favourable and unfavourable growing seasons. Leaf traits differed widely in the degree of seasonal variation displayed. Leaf mass per unit area ( M a ) showed none. At the other extreme, seasonal variation accounted for nearly a third of total variability in dark respiration ( R dark ). At the non‐tropical sites, carboxylation capacity ( V cmax ) at the prevailing growth temperature was typically higher in summer than in winter. When V cmax was normalized to a common reference temperature (25°C), however, the opposite pattern was observed for about 30% of the species. This suggests that metabolic acclimation is possible, but far from universal. Intraspecific variation—combining measurements of individual plants repeated at contrasting seasons, different leaves from the same individual, and multiple conspecific plants at a given site—dominated total variation for leaf metabolic traits V cmax and R dark . By contrast, site location was the major source of variation (53%) for M a . Interspecific trait variation ranged from only 13% of total variation for V cmax up to 43% for nitrogen content per unit leaf area. These findings do not support a common practice in DGVMs of assigning fixed leaf trait values to plant functional types. Trait‐based models should allow for interspecific differences, together with spatial and temporal plasticity in leaf structural, chemical and metabolic traits. A plain language summary is available for this article. Abstract : Plain Language Summary